(untitled) (Journal of Economic Research & Business Administration, 2015)
The article discusses the role and importance of the transport complex , in particular rail transport in the development of Kazakhstan’s economy in the economic crisis . also paid on the key economic indicators and investment in the field of railway transport , the main directions of Kazakhstan transport strategy .